Reforma a vapor do metano sobre catalisadores de Pt-Ni/α-Al2O3: efeito das condições de síntese e do teor da Pt nas propriedades de oxi-redução, estruturais e catalíticas - Souza, Vivian Passos de (2011)
In recent years, the demand for hydrogen has increased considerably in Petrobras refineries, due to the installation of fuel hydrotreating units. These units are necessary to meet new quality standards, which are imposed by environmental concerns. Steam reforming is the most common process to produce hydrogen and synthesis gas. The catalyst used in this process has nickel as the active phase, supported in refractory material, such as alpha-alumina. These catalysts are most cost-effective, when compared to others with higher activity. On the other hand, the promotion of them with small amounts of noble metal can provide interesting characteristics, without greatly affecting their final cost. The catalyst at the top of the reformer is easily oxidized, either during unplanned shutdowns, or even during normal operation, if hydrogen is absent. The use of Pt as a promoter has been studied in the literature, and the results show its effect in decreasing the reduction temperature of nickel catalysts. Additionally, the catalysts at the top of the reformer (20-40%) are more prone to coking. The objective of this study is to evaluate how preparation conditions and platinum content affect the Ni/α-Al2O3 catalysts, regarding reduction and oxidation of the catalysts, and also their activity, stability and coke formation. The catalysts were evaluated under conditions which are characteristic of the top region of an industrial reformer. The catalysts were prepared with different contents of platinum, 0.01% and 0.3% wt, at different calcination temperatures after impregnation of nickel and platinum . It was observed that Pt increases the reducibility of catalysts with 10% wt of Pt, calcined at 600 and 800°C, as long as the final catalyst, after Pt impregnation, was calcined at low temperature. At higher temperatures, sintering of Pt takes place, suppressing its effect. An increase of calcination temperature of the NiO/α-Al2O3 catalyst from 600 to 800°C does not cause a considerable decrease of the Pt effect on the reduction. When the NiO/α-Al2O3 catalyst was calcined at 1000°C, the effect of Pt became insignificant. The Pt increases the reducibility of the catalyst even at levels as low as 0.01%wt, although its effect is greater when a higher content is used. This behavior is observed for the reduction, using H2 as well as H2 + H2O (v) or CH4 + H2O (v). The reduction with methane and steam occurs at higher temperature, but faster. In this case, it is assumed that as the Ni° atoms are generated at short distances from each other, diffusion over the support surface is easier, enhancing their nucleation into nickel metal clusters. The presence of Pt also minimizes the formation of species with greater support interaction, even when the final catalyst is subjected to oxidation at high temperatures (900°C). The promotion with 0.3% wt of Pt minimizes coke formation. This behavior is attributed to changes in the surface structure of the catalyst or in the reaction rate of coke formation. Apparently, for the catalyst with 0.01% wt of Pt, this small amount of Pt would be insufficient to cause any structural changes or variation in the rate of coke formation. This behavior was found in tests under conditions that enhance coke formation and also under normal conditions of catalytic evaluation. The catalytic evaluation including a reduction step with H2 and CH4 + H2O (v) and the thermogravimetric analysis for assessment of coke formation,demonstrated that the promotion with platinum leads to a greater activity of the nickel catalyst in the catalytic systems or test conditions where reducing the catalyst and/or the ability to keep it in the reduced state is a determinant factor.